Lipopolysaccharides induced inflammatory responses and electrophysiological dysfunctions in human-induced pluripotent stem cell derived cardiomyocytes - Yücel, Gökhan; Zhao, Zhihan; El-Battrawy, Ibrahim; Lan, Huan; Lang, Siegfried; Buljubasic, Fanis; Utikal, Jochen; Wieland, Thomas; Borggrefe, Martin; Zhou, Xiao-Bo; Akın, Ibrahim (Scientific reports, 2017)
Severe infections like sepsis lead frequently to cardiomyopathy. The mechanisms are unclear and an optimal therapy for septic cardiomyopathy still lacks. The aim of this study is to establish an endotoxin-induced inflammatory model using human induced pluripotent stem cell (hiPSC) derived cardiomyocytes (hiPSC-CMs) for mechanistic and therapeutic studies. hiPSC-CMs were treated by lipopolysaccharide (LPS) in different concentrations for different times. ELISA, FACS, qPCR, and patch-clamp techniques were used for the study. TLR4 (Toll-like receptor 4) and its associated proteins, CD14, LBP (lipopolysaccharide binding protein), TIRAP (toll-interleukin 1 receptor domain containing adaptor protein), Ly96 (lymphocyte antigen 96) and nuclear factor kappa B as well as some pro-and anti-inflammatory factors are expressed in hiPSC-CMs. LPS-treatment for 6 hours increased the expression levels of pro-inflammatory and chemotactic cytokines (TNF-a, IL-1ß, IL-6, CCL2, CCL5, IL-8), whereas 48 hour-treatment elevated the expression of anti-inflammatory factors (IL-10 and IL-6). LPS led to cell injury resulting from exaggerated cell apoptosis and necrosis. Finally, LPS inhibited small conductance Ca2+-activated K+ channel currents, enhanced Na+/Ca2+-exchanger currents, prolonged action potential duration, suggesting cellular electrical dysfunctions. Our data demonstrate that hiPSC-CMs possess the functional reaction system involved in endotoxin-induced inflammation and can model some bacterium-induced inflammatory responses in cardiac myocytes.
Gesehen am 18.08.2017